Forgiveness Therapy Untuk Meningkatkan Subjective Well-Being Pada Perempuan Korban Kekerasan Verbal Dalam Rumah Tangga - Murdani, Bayu; Astuti, Kamsih (Jurnal Psikologi TALENTA, 2024)
Verbal abuse has an impact on decreasing life satisfaction and increasing negative affect among women in the household. Forgiveness therapy is a therapeutic method to improve subjective well-being. The purpose of the study was to determine the effect of forgiveness therapy on improving subjective well-being in women victims of domestic verbal violence. The participants in the study were 5 housewives who experienced verbal violence and had low and moderate subjective well-being. This study used a pre-experimental research design the one group pretest posttest design. There are 4 phases of forgiveness therapy used in the study, namely uncovering anger and hurt phase, decision phase, working phase, deeping phase. The paired sample t-test assumption test shows that there is no difference in the application of forgiveness therapy at pretest and posttest with a score of Z = 0.606 (>0.05). There is a difference in the improvement of subjective well being at the time of posttest and follow-up to participants with a subjective well-being scale with a score of t = -2.701 p = 0.025 (<0.05). Based on these results, it can be concluded that there is an effect of providing forgiveness therapy on improving the subjective well-being of female victims of domestic verbal violence.